Identification, characterization and expression analysis of hepcidin gene in sheep - Radial, Peres R. [UNESP]; Oliveira Filho, Jose P. [UNESP]; Cunha, Paulo Henrique J. [UNESP]; Cagnini, Didier Quevedo [UNESP]; Araujo, Joao P. [UNESP]; Winand, Nena J.; Borges, Alexandre Secorun [UNESP] (Elsevier B.V., 2011)
Hepcidin is part of the innate immune system, and it plays a central role in the regulation of iron homeostasis. This peptide has been previously characterized in man, non-human primates, rat, mouse, dog, swine, cattle, horse, fishes, reptiles and birds but until now not in sheep. The aim of this study was to sequence, characterize and perform hepcidin expression analysis in different tissues collected from healthy sheep. The resulting open reading frame consisted of 249 bp predicted to encode an 82 aa peptide with a putative 23 aa signal peptide, a 34 aa pro-region and the 25 aa mature hepcidin. The deduced sequence of the sheep hepcidin precursor was most homologous to Bos taurus and Bubalus bubalis. Hepcidin was predominantly expressed in liver, although high expression was present in abomasum and lower level expression occurred in other tissues. These findings extend our comparative knowledge showing the relationship of sheep hepcidin to other mammalian hepcidins and will be helpful for additional studies on iron metabolism and inflammatory processes in sheep. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Sheep; Hepcidin; mRNA; Peptide; Innate immunity